Isolated jejunal necrosis following corrosive acid poisoning - Gaur, Naveen Kumar; Shaikh, Oseen Hajilal; Vijayakumar, Chellappa; Kumbhar, Uday Shamrao (International Surgery Journal, 2021)
Corrosive acid poisoning is common in Asian countries, and most of the time, it is of suicidal intent in adults. Commonly they lead to extensive injuries of the upper gastrointestinal tract, and isolated involvement of the lower gastrointestinal tract is rare. We present a 35-year-old male who presented to us with a history of corrosive acid ingestion mixed with alcohol. Imaging did not demonstrate any pneumoperitoneum. The patient underwent exploratory laparotomy and found to have isolated jejunal necrosis without any evidence of injury to the stomach and duodenum. Segmental resection and end-to-end anastomosis were done.